The Effect Of Peer Social Support On Fear Of Failure In Academic Assignments Among Students In Medan City - Sianipar, Raju; Rosito, Asina Christina (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine the influence of peer social support on fear of failure in academic assignments among students in Medan City. Based on the results of research on the influence of peer social support on fear of failure in students in Medan, it can be concluded as follows: Regression analysis shows that peer social support influences 54.5% (R² = 0.545) of fear of failure in students' academic assignments in Medan. The remaining 45.5% is influenced by other factors outside the research model. This result indicates a positive relationship: the higher the social support received, the higher the level of fear of failure experienced by students. The results of the statistical test show a t value of 20.430, while the t value in the table with 348 degrees of freedom is 1.649. because the calculated t value (20.430) is greater than the t value in the table (1.649), the null hypothesis (Ho) is rejected. This means that there is a significant influence between peer social support on fear of failure in students' academic assignments. A total of 317 respondents (90.6%) of students in Medan have a high level of peer social support. In parallel, 316 respondents (90.3%) were in the high category for fear of failure, indicating that the majority of students experienced both conditions simultaneously.